2021
DOI: 10.3390/ma14030518
|View full text |Cite
|
Sign up to set email alerts
|

Graphene/MoS2 Nanohybrid for Biosensors

Abstract: Graphene has been studied a lot in different scientific fields because of its unique properties, including its superior conductivity, plasmonic property, and biocompatibility. More recently, transition metal dicharcogenide (TMD) nanomaterials, beyond graphene, have been widely researched due to their exceptional properties. Among the various TMD nanomaterials, molybdenum disulfide (MoS2) has attracted attention in biological fields due to its excellent biocompatibility and simple steps for synthesis. According… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 167 publications
(88 reference statements)
0
20
0
Order By: Relevance
“…The same occurs to S2p, it shrinks for MoS2, and a sulfur doublet shows up at higher binding energy. The S2p3/2 line appearing at 169.6 eV is attributed to S 6+ in sulfates (SO4) 2 , which can be explained by either MoO2(SO4) or Mo(SO4)3 formation at the surface of MoS2. Moreover, it was observed some sulfur loss at the surface near region, which may be due to the formation of volatile sulfur compounds during heat treatment.…”
Section: Characterization Of Flower-like Mos 2 -Peg/aumentioning
confidence: 99%
See 1 more Smart Citation
“…The same occurs to S2p, it shrinks for MoS2, and a sulfur doublet shows up at higher binding energy. The S2p3/2 line appearing at 169.6 eV is attributed to S 6+ in sulfates (SO4) 2 , which can be explained by either MoO2(SO4) or Mo(SO4)3 formation at the surface of MoS2. Moreover, it was observed some sulfur loss at the surface near region, which may be due to the formation of volatile sulfur compounds during heat treatment.…”
Section: Characterization Of Flower-like Mos 2 -Peg/aumentioning
confidence: 99%
“…However, the main feature that must be considered to a given material be used in biomedical proposals is its physicochemical stability and biological safety [1]. In this context, molybdenum disulfide (MoS 2 ) and its derivatives have attracted attention due to its excellent biocompatibility and simple synthesis [2]. The 2D nanomaterials have been used in the diagnosis and therapy of cancer [3] especially when they are combined with gold nanoparticles [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, several published review articles have explored the production process, physical and chemical properties, as well as applications of graphene-based materials, which can be used in diversified application areas [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. However, almost all primarily focused on a single application field and studied the material development, their characteristics, and applications only for that particular area, for example, sensors and biosensors [ 53 , 54 , 55 , 56 ], energy storage and supercapacitors [ 57 , 58 , 59 , 60 , 61 , 62 ], and biomedical and drug delivery [ 63 , 64 , 65 , 66 ]. There is a scarcity of review articles on graphene-based materials to comprehensively cover all the production processes of graphene derivatives such as pure and composite graphene fibres, graphene/polymer composite (gPCs), and graphene/fibre/polymer composites (gFPCs), and their applications in various fields such as energy, wearable technology, agriculture, wastewater treatment, medical, healthcare, and in the automobile industry.…”
Section: Introductionmentioning
confidence: 99%
“…Inside the 2D hexagonal carbon nanotube lattice, the three electron valences are bonded to other carbon atoms while a single π electron shows very high mobility with quantum property in the 3D space and consequently outstanding conductivity, which has made these materials the most studied for electrical or electrochemical sensors [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inside the 2D hexagonal carbon nanotube lattice, the three electron valences are bonded to other carbon atoms while a single π electron shows very high mobility with quantum property in the 3D space and consequently outstanding conductivity, which has made these materials the most studied for electrical or electrochemical sensors [5]. Numerous research works for water pollutant removal such as Cr(VI) have been undertaken and demonstrated that at pH = 1, the redox reaction occurs with the formation of less toxic Cr(III), meanwhile at pH = 7, the absorption process takes place on the carbon nanotube multi-walled surface [6].…”
Section: Introductionmentioning
confidence: 99%